Effects of actual and perceived financial literacy skills on financial well-being at retirement - Voros, Zsofia; Szabo, Zoltan; Schepp, Zoltán; Kehl, Daniel; Kovacs, Oliver Bela (Marketing & Menedzsment, 2021)
THE AIMS OF THE PAPER Studies have not explained fully how financial literacy, decision making skills and the diverse forms of financial literacy overconfidence interact with each other to explain households’ actual and perceived financial well-being at retirement. This study aims to map the interactions among these constructs within the elderly population. METHODOLOGY In the framework of a larger assessment on subjective well-being and its antecedents at retirement, three hundred retired people between the age of 65 and 85 filled out a questionnaire in their home in Hungary in March 2019. MOST IMPORTANT RESULTS Elderly people are overconfident in their financial literacy skills both on absolut and relative levels. Percieved financial literacy is a better predictor of financial situation than actual financial literacy. However, financial literacy overconficence relative to others harms elderly people’s financial situation. Subjective financial well-being is mainly driven by the actual financial situation. Decision making skills play an important role in the calibration of financial literacy skills and have an additional direct effect on the subjective level of financial well-being. Our outcomes reinforce that it is indeed worth promoting programs helping elderly people acquiring domain-specific financial knowledge. These programs may lead to better financial situation and higher self-efficacy. Moreover, our findings imply that it would be worthwhile for programs to concentrate on the calibration of financial knowledge vis-á-vis others. RECOMMENDATIONS To complement the mainstream literature, the study examines the forms of overconfidence and their effects on financial well-being separately and concentrates on the elderly population. Acknowledgements: The project was financed by the European Social Fund: Comprehensive Development for Implementing Smart Specialization Strategies at the University of Pecs (EFOP-3.6.1.- 16-2016-00004). Declarations of interest: none.